Gaya Hidup dalam Media Sosial - Intan, Theresia; Akhsaniyah, Akhsaniyah; Tiananda, Febriyan (Universitas Serang Raya, 2019)
This study describes how lifestyles are representated on social media. Audience observeinformation produced by the media as it is a main source and it is a significant part indetermining lifestyles. Lifestyle reflects the whole person who interacts with the environment.Mass media has an influence on lifestyle. This research will use the Virtual Ethnographymethod, is a methodology for investigating the internet in order to be able to exploreempirically its current use. The two informants were in the process of building character as afigure of a rich person with a harmonious family and as a romantic husband. It is notuncommon for the two informants to highlight what they have with a bit of exaggeration or howhe enjoys the holidays, it is not explained that almost the average vacation is financed by alarge family and friends. directing the identity of the informant 2 as a material overload,informants often upload celebratory activities carried out for his wife, their children and manyattend the events held. Vacation photos are almost done every 3 times a month. In conductingconversations, the informants were happy with the responses of many people or comments whowere curious about the tourist destinations visited or how much they spent